(untitled) (The Macau Ricci Institute Journal, 2018)
Online Peer-to-Peer (P2P) lending schemes began to flourish in China in 2015. This lending model, where lender and borrower could do transactions without involving banking institutions, was welcomed by many start-ups and entrepreneurs because it provided an effective solution for reaching borrowers directly. One of these borrower classes was college students. Campus loans, facilitated through P2P platforms, quickly became popular. However, after a series of university scandals, questions emerged as tothe morality of the industry and the responsibility of the P2P platforms within it to guard against abuses inflicted upon college students and the borrower market as a whole.